Why SNP rs227584 is associated with human BMD and fracture risk? A molecular and cellular study in bone cells. Issue 2 (28th October 2018) - Zhou, Xu; Qiu, Ying‐Hua; He, Pei; Jiang, Fei; Wu, Long‐Fei; Lu, Xin; Lei, Shu‐Feng; Deng, Fei‐Yan
Abstract: A large number of SNPs significant for osteoporosis (OP) had been identified by genome‐wide association studies. However, the underlying association mechanisms were largely unknown. From the perspective of protein phosphorylation, gene expression regulation, and bone cell activity, this study aims to illustrate association mechanisms for representative SNPs of interest. We utilized public databases and bioinformatics tool to identify OP‐associated SNPs which potentially influence protein phosphorylation (phosSNPs). Associations with hip/spine BMD, as well as fracture risk, in human populations for one significant phosSNP, that is, rs227584 (major/minor allele: C/A, EAS population) located in C17orf53 gene, were suggested in prior meta‐analyses. Specifically, carriers of allele C had significant higher BMD and lower risk of low‐trauma fractures than carriers of A. We pursued to test the molecular and cellular functions of rs227584 in bone through osteoblastic cell culture and multiple assays. We identified five phosSNPs significant for OP ( P < 0.01). The osteoblastic cells, which was transfected with wild‐type C17orf53 (allele C at rs227584, P126), demonstrated specific interaction with NEK2 kinase, increased expression levels of osteoblastic genes significantly ( OPN, OCN, COL1A1, P < 0.05), and promoted osteoblast growth and ALP activity, in contrast to those transfected with mutant C17orf53 (allele A at rs227584, T126). In the light of the consistent evidences between the present functional study in human bone cells and the prior association studies in human populations, we conclude that the SNP rs227584, via altering protein‐kinase interaction, regulates osteoblastic gene expression, influences osteoblast growth and activity, hence to affect BMD and fracture risk in humans.